Personality and Counterproductive Work Behavior: The Mediating Role of Job Stress - Cucuani, Hijriyati; Ramadhani, Ifi Anjely (LPPM Universitas 17 Agustus 1945 Samarinda, 2025)
Counterproductive work behavior is often associated with work stress, which tends to be more easily experienced by employees with certain personalities. This study aims to see the relationship between personality and counterproductive work behavior mediated by work stress. The subjects of the study were 147 employees in the Pekanbaru government offices. Data were collected using the IPIP-BFM-50 Scale, the Counterproductive Work Behavior Checklist for counterproductive behavior and the work stress scale. Based on the path analysis test with the JASP 0.18.3 program, it is known that work stress fully mediates the effect of extraversion on counterproductive work behavior and partially mediates the effect of neuroticism on counterproductive work behavior. While agreeableness, conscientiousness and openness to change were not related to counterproductive work behavior. This finding can provide an overview for human resource management to consider personality in employees placing in certain types and conditions of work stress to prevent counterproductive behavior. In addition, management can also determine the right program to manage work stress so as to minimize counterproductive behavior.